Nutrition and lipidomic profile in colorectal cancers - Notarnicola, Maria; Caruso, Maria Gabriella; Tutino, Valeria; De Nunzio, Valentina; Gigante, Isabella; De Leonardis, Giampiero; Veronese, Nicola; Rotolo, Ornella; Reddavide, Rosa; Stasi, Elisa; Miraglia, Chiara; Nouvenne, Antonio; et al. (Acta Biomedica Atenei Parmensis, 2018)
Background: Adherence to a healthy diet has been reported to be essential for the primary prevention of colorectal cancer, through a reduction of tissue inflammation, a low concentration of circulating lipoproteins and lower levels of serum cholesterol. Since an altered expression of the fatty acids pattern has been demonstrated to be a crucial event in colorectal carcinogenesis, lipidomic analysis is considered able to identify early diagnostic and prognostic biomarkers of complex diseases such as colorectal cancer. Methods: cell membrane fatty acid profile and serum lipoproteins pattern were evaluated by gas chromatography and electrophoresis method respectively. Results: There is a close association between diet and lipidomic profile in colorectal cancer, both in pre-clinical and clinical studies. A modified serum lipoproteins pattern has been demonstrated to be predominant in intestinal tumors. Conclusions: The study of fatty acids profile in cell membrane and the evaluation of serum lipoproteins subfractions could be useful to have an integrate vision on the interactions between lipids and the pathogenesis of colorectal cancer and to understand the mechanisms of action and the consequences of these interactions on human health status.